2018
DOI: 10.1007/s10071-018-1220-0
|View full text |Cite
|
Sign up to set email alerts
|

Sight or smell: which senses do scavenging raptors use to find food?

Abstract: Raptors are usually considered to be mainly visually dependent, and the use of other sensory modalities has rarely been studied in these birds. Here, we investigated experimentally which senses (vision and/or olfaction) Turkey vultures (Cathartes aura) and Southern caracaras (Caracara plancus) use to find hidden food. First, two identical stainless-steel perforated balls, one containing a putrefied piece of meat and the other an odorless control, were presented to birds in binary choice experiments. Both speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 61 publications
0
23
2
Order By: Relevance
“…The species that first detected more carcasses was the turkey vulture, followed by the southern caracara. These two species are not only guided by the sense of sight and hearing, like most raptors, but also have a developed sense of smell (Houston, 1985; Potier et al, 2019). It has been hypothesized that these evolutionary differences between New and Old world vulture guilds (e.g., olfactory capacities of some species) are due to the type of habitat in which they have evolved; Old World vultures are distributed in areas of open habitat, while most New World species (except the two condor species) are mainly distributed in Neotropical forests (Houston, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species that first detected more carcasses was the turkey vulture, followed by the southern caracara. These two species are not only guided by the sense of sight and hearing, like most raptors, but also have a developed sense of smell (Houston, 1985; Potier et al, 2019). It has been hypothesized that these evolutionary differences between New and Old world vulture guilds (e.g., olfactory capacities of some species) are due to the type of habitat in which they have evolved; Old World vultures are distributed in areas of open habitat, while most New World species (except the two condor species) are mainly distributed in Neotropical forests (Houston, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In the Cerrado, there are five of the seven species of the New World vultures (Cathartidae): turkey (Cathartes aura), lesser yellow-headed (C. burrovianus), greater yellow-headed (C. melambrotus), American black (Coragyps atratus), and king (Sarcoramphus papa) vultures. A characteristic feature of some of these vulture species is their developed sense of smell, as they have highly developed olfactory bulbs, which is not found in any of the Old World vulture species (Potier et al, 2019). This ability, together with the potential to fly great distances with little energy expenditure (Duriez et al, 2014), means that New World vultures are especially efficient at locating carrion even when vegetation is dense.…”
Section: Despite the Enormous Biodiversity Hosted In The Brazilianmentioning
confidence: 99%
“…As a result, natural selection has shaped foraging strategies and animals' physical, physiological, or neurological adaptations to increase search efficiency and food acquisition rates (Preston, Pitchford, & Wood, 2010). In birds, many species rely on visual and/or olfactory cues while foraging (Goldsmith, 1990;Martin, 2017;Nevitt & Bonadonna, 2005;Potier, Duriez, Célérier, Liegeois, & Bonadonna, 2019). Although sound is important in the behavioral ecology of many birds (e.g., mate finding, territorial displays), few species reportedly use auditory cues during foraging (e.g., Wagner, Kettler, Orlowski, & Tellers, 2013;Onrust et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Avian dietary specialization differs considerably, however, as can be illustrated by the vultures inhabiting African savanna ecosystems. Unlike species of New World vultures (Cathartidae) (Potier et al, 2019), Africa's vultures (Accipitridae) reportedly have no refined olfactory senses (Houston, 1985). However, closely related species are able to use olfaction during foraging (Gilbert & Chansocheat, 2006;Nelson Slater & Hauber, 2017;Potier, 2019), indicating that it might be possible for the African species too.…”
Section: Introductionmentioning
confidence: 99%
“…Further, much recent behavioral work has demonstrated that birds use odor in many important ecological contexts, such as in mate choice and species recognition (Bonadonna and Mardon 2013, Zhang et al 2013, Van Huynh and Rice 2019, kin recognition (Fracasso et al 2019), predator avoidance (Amo et al 2008, Roth et al 2008, Stanbury and Briskie 2015, Lee 2021, nesting (Petit et al 2002, Gwinner and Berger 2008, Shutler 2019, foraging (Hutchinson and Wenzel 1980, Hiltpold and Shriver 2018, Saavedra and Amo 2018a, Potier et al 2019, Potier 2020, and navigation (Pollonara et al 2015, Abolaffio et al 2018, Zannoni et al 2020. Here, we assess the ability for birds to cue in on plant volatiles to locate insect prey.…”
Section: Introductionmentioning
confidence: 99%